Hand heating lowers postprandial blood glucose concentrations: A double-blind randomized controlled crossover trial. (March 2020) - Moore, Jeff; Kressler, Jochen; Buono, Michael J.
Highlights: Hand heating lowers postprandial blood glucose (PBG). No difference was seen between hand heating and hand heating with negative pressure. The effect of hand heating on FBG and PBG oppose those of whole-body heat therapy. Abstract: Objectives: Examine effect of single hand heating with and without negative pressure on fasting blood glucose (FBG) and postprandial blood glucose (PBG). Design: Double-blind randomized controlled trial with crossover design. Subjects: FBG experiment: 17 healthy subjects (4 males). PBG experiment: 13 healthy subjects (1 males). Interventions: Devices included one providing heat only, one heat and negative pressure, and one acting as a sham. For the FBG experiment the devices were used for 30 min. For the PBG experiment the devices were used for one hour during an oral glucose tolerance test (OGTT). Outcome Measures: Blood glucose measurements were used to determine change in FBG, peak PBG, area under the curve (AUC), and incremental AUC (iAUC). Results: Temperature: Change in tympanic temperature was ≤ 0.15 °C for all trials. FBG: There was no effect on FBG. PBG: Compared to the sham device the heat plus vacuum and heat only device lowered peak blood glucose by 16(31)mg/dL, p = 0.092 and 18(28)mg/dL, p = 0.039, respectively. AUC and iAUC: Compared to the sham device, the heat plus vacuum device and heat only device lowered the AUC by 5.1(15.0)%, p = 0.234 and 7.9(11.1)%, p = 0.024 respectively and iAUC by 17.2(43.4)%, p = 0.178 and 20.5(34.5)%, p = 0.054, respectively. Conclusions: Heating a single hand lowers postprandial blood glucose in healthy subjects.